How do you solve # x-sqrt(2x+3) =-2#?

1 Answer
Apr 17, 2016

Answer:

Isolate the square root.

Explanation:

#x + 2 = sqrt(2x + 3)#

Square both sides of the equation to get rid of the square root.

#(x + 2)^2 = (sqrt(2x + 3))^2#

#x^2 + 4x + 4 = 2x + 3#

#x^2 + 2x + 1 = 0#

#(x + 1)(x + 1) = 0#

#x = -1#

Checking your solution in the original equation, we find our solution works. This is vital with radical equations, since extraneous solutions can arise during the solving process.

Hopefully this helps!